The Probiotic Effect towards Aspirin-induced Gastric Ulcer Healing Process as Measured by Mucous Thickness, Reepithelization, Gastric Glands Formation, and Angiogenesis in Animal Model - Lucretia, Teresa; Achadiyani, Achadiyani; Masria, Sadeli (Maranatha Christian University, 2016)
Gastric Ulcer is a common side effect of Non-Steroid Anti Inflammatory Drugs (NSAIDs) use such as Aspirin. Probiotic has many benefits especially for the alimentary system, but the effect on gastric ulcer have yet to be explored. In this research we aimed to find the probiotic effect on histological structure changes during aspirin induced gastric ulcer healing process in animal model. This was simple random sampling animal experimental laboratory, that divided Wistar Rats into two main groups. Both groups were induced with Aspirin (300mg/Kg BW) per oral, once daily for three consecutive days,and subsequently the test group were given probiotic suspension (cfu >108/gr) per oral, once daily, for 14 days. Each subgroups were sacrified serially at day 0, 3, 7, 14. The gaster were collected and processed for histology examination. Better histological structures were shown in the test group at day 14. MANOVA result showed probiotics effect in enhancing histological structure changes during gastric ulcer healing process. Better histological structure changes were observed in mucus thickness; reepitelization, gastric glands formation, and angiogenesis process of the test group. As a conclusion, probiotic enhanced mucus thickness, reepitelization, glands remodelling, and angiogenesis in Aspirin induced gastric ulcer healing process in animal model.Â Key words: probiotic, gastric ulcer, histological structure, aspirin, healing process